Optimal management of electric vehicle charging loads for enhanced sustainability in shared residential buildings - Almutairi, Abdulaziz; Albagami, Naif; Almesned, Sultanh; Alrumayh, Omar; Malik, Hasmat (Frontiers in Energy Research, 2024)
Demand management of electric vehicles (EVs) in shared residential parking lots presents challenges for sustainable transportation systems. Especially, in shared parking lots where multiple EVs share the same parking space, such as residential apartments. This is challenging due to involvement of various factors such as limited number of chargers, limited capacity of transformer, and diverse driving behavior of EV owners. To address this issue, this study proposes an optimal demand management framework that addresses limited chargers, transformer capacity, and diverse driving behavior to promote sustainable EV integration. By estimating driving behavior, energy consumption, and utilizing a linear programming-based optimization model, power allocation to EVs is optimized based on multiple factors. A satisfaction index is introduced to measure the satisfaction level of the EV community, further emphasizing user-centric sustainability. Performance analysis includes factors such as power usage, charger utilization, and community satisfaction. The performance of the proposed method is compared with a conventional method and the proposed method increase the satisfaction index of the community by up to 10%. In addition, sensitivity analysis is used to explore the impact of factors like charger availability, EV penetration, and transformer capacity limits. Results show that with 3% EV penetration, satisfaction levels exceed 75%, reaching over 80% with five chargers and 6% EV penetration.